2013
DOI: 10.1053/j.jrn.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Prealbumin is Associated With Visceral Fat Mass in Patients Receiving Hemodialysis

Abstract: Objective Albumin and prealbumin are associated with nutritional status and inflammatory status. Each has a residual effect on mortality outcomes when included in regression models that include the other. Prealbumin is increased in the obese mouse model as a consequence of stabilization of prealbumin by Retinol Binding Protein 4 (RTB4), secreted by adipocytes. We carried out this study to establish the contribution of adiposity to prealbumin levels in prevalent dialysis patients and the relationship of prealbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Possibly, the malabsorption of vitamin K is more prominent in our patients who purely restrict than in those who may binge on fatty and protein‐containing foods (even if they purge soon after), and thus AN‐R, high INR, and low prealbumin co‐occur. Despite the fact that prealbumin has been correlated with visceral fat mass in a hemodialysis population, there was no significant difference in the percent body fat as measured by lipodystrophy analysis between the low prealbumin and normal prealbumin groups in our study …”
Section: Discussioncontrasting
confidence: 74%
“…Possibly, the malabsorption of vitamin K is more prominent in our patients who purely restrict than in those who may binge on fatty and protein‐containing foods (even if they purge soon after), and thus AN‐R, high INR, and low prealbumin co‐occur. Despite the fact that prealbumin has been correlated with visceral fat mass in a hemodialysis population, there was no significant difference in the percent body fat as measured by lipodystrophy analysis between the low prealbumin and normal prealbumin groups in our study …”
Section: Discussioncontrasting
confidence: 74%
“…We also used normalized protein catabolic rate (nPCR) (grams per kilogram per day) calculated from dialysis kinetic modeling during the month that body composition was measured as an estimate of dietary protein intake (13). In the course of evaluation, we also asked patients whether they had experienced any changes in body weight during the previous six months.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that both serum albumin and creatinine concentrations are associated with measures of protein intake (normalized Protein Catabolic Rate (nPCR) and inflammation (CRP) cross-sectionally and longitudinally 27,28 . Similarly, prealbumin concentration was associated also with nPCR and inflammatory biomarkers 29 .…”
Section: Discussionmentioning
confidence: 89%